2001
DOI: 10.1097/00005537-200107000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed‐Dye Laser and Retinoic Acid Delay Progression of Oral Squamous Cell Carcinoma: A Murine Model

Abstract: This study demonstrated the superiority of a single treatment with the PDL coupled with retinoic acid to delay the progression of cancer when compared with treatment with retinoic acid alone, thus introducing a novel strategy in cancer control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Possibly, viral infections in VAD animals contribute to the development of pre-neoplastic changes in the lung that can, in some cases, progress to high-grade dysplasia and carcinoma [ 60 , 61 ]. The relationship between lung cancer and vitamin A precursors has been previously examined [ 62 , 63 , 64 , 65 , 66 ], and (as for other cancers) vitamin supplementation as a treatment for lung cancer has yielded variable results [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, viral infections in VAD animals contribute to the development of pre-neoplastic changes in the lung that can, in some cases, progress to high-grade dysplasia and carcinoma [ 60 , 61 ]. The relationship between lung cancer and vitamin A precursors has been previously examined [ 62 , 63 , 64 , 65 , 66 ], and (as for other cancers) vitamin supplementation as a treatment for lung cancer has yielded variable results [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings show that problems of potency or toxicity are likely to attend the use of any single strategy, and multiple strategies, synergizing each other, offer an exciting new option for cancer prevention [12]. Our previous studies indicate that the efficacy of tumor treatment is significantly improved when PDL is combined with retinoic acid [13]. The same principle should hold true when PDL is combined with Celecoxib.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous studies in animal models have indicated a significant inhibitory effect in oral squamous cell carcinoma from PDL. 11 However, our success in using the laser MVT treatment is limited to nude mice bearing tumor by skin inoculation of oral squamous cell carcinoma. This model certainly provides the most expedient means of establishing the feasibility and efficacy of the new combined treatment.…”
Section: Discussionmentioning
confidence: 99%